Smart Apps Creator-Based Islamic Mobile Learning Application for Strengthening Religious Literacy among Senior High School Students - Achmad Faqihuddin; Indah Sari; Edi Suresman; Fahmi Fazar; Faisal Fauzan Ilyasa; Muflih, Abdillah (Jurnal Pendidikan Agama Islam, 2026)
Purpose – This study aims to develop an Islamic Mobile Learning Application (IMLA) utilizing Smart Apps Creator to enhance religious literacy in Islamic Religious Education for senior high school students. The application was developed to address monotonous teaching methods, limited access to interactive learning media, and the increasing need for engaging digital learning tools. Design/methods/approach – The study employed a Research and Development (R&D) approach using the ADDIE model. Data were collected through structured interviews with Islamic Religious Education teachers, expert validation by five learning media experts, classroom observations, and pretest–post-test assessments involving 100 students selected through convenience sampling. The application was developed using Smart Apps Creator 3 in Android format and designed with interactive multimedia features. Findings –   The development process yielded a feasible and interactive IMLA comprising five curriculum-based learning modules, videos, quizzes, animations, evaluation tasks, references, and developer information. Expert validation indicated excellent content validity, with a Content Validity Index (CVI) of 1.00 across visual design, navigation, accessibility, content relevance, and multimedia interactivity. Implementation results showed a statistically significant improvement in students’ religious literacy, with mean scores increasing by 12.11 points from pretest to post-test. The paired-samples t-test and the high pretest–post-test correlation further supported the robustness of this improvement. Research implications/limitations – This study was limited by its context-specific implementation and the absence of a control group. Future studies may examine the long-term impact of IMLA in broader educational settings. Originality/value – This study contributes a Smart Apps Creator-based Islamic mobile learning application specifically designed to strengthen religious literacy and support more meaningful, accessible, and engaging Islamic Religious Education learning experiences.